Techno-economic Guidelines for Choosing between BESS and Gas Turbine - Ruotsala, Viivi (My University, 2021)
Goal for the thesis was to find out if it is economically and technically possible for battery storage system (BESS) to replace gas turbine (GT) which is used for peak loads. Study was made for two different sizes of GTs (25MW and 104MW) and for four different sizes of BESS’(25MW/25MWh, 25MW/100MWh, 104MW/104MWh and 104MW/416MWh) in two different countries in Belgium and in Ireland. Study answers the questions: What services GT and BESS can offer? What are the annualized costs, net present value (NPV), internal rate of return (IRR) and payback for two different sizes of GTs in Belgium and in Ireland? What are the annualized costs, NPV, IRR and payback for four different sizes of BESS’ in Belgium and in Ireland? What kind of services BESS can offer to make it profitable? What are the situations when BESS can/should replace GT or not? In which scenario it is economically and technically possible to replace GT with BESS? As the background for this study different types of GTs and storages were introduced, grid structure and applications were presented, and cost structure for BESS and GT and electricity markets were described. Data for study was collected from two existing gas turbines, researches, reports, literature, and public data sources. In Belgium, different system service markets and in Ireland, system service markets and intraday market were analyzed. Analysis for different markets in Belgium and in Ireland was conducted by a rule-based Excel model and the sensitivity analysis was conducted by BESS’ capital expenditures and discount rates of 0% and 4%. Results of the study showed that it is technically possible for BESS to replace GT used for peak loads, except in one four hours’ case where 104MW/104MWh BESS’ capacity was exceeded. In Belgium it is economical invest in the 25MW/25MWh and the 25MW/100MWh BESS’ if they are offering multiple services and in-vestment prices are 450€/kWh, 350€/MWh or 200€/kWh. If multiple services are provided by 104MW/104MWh and 104MW/416MWh BESS’ with the investment price of 200€/kWh, the investment is profitable. In Ireland, it is profitable to invest in 25MW/25MWh and 104MW/104MWh BESS’ even with current prices with the help of the DS3 program. But when 25MW/100MWh and 104MW/416MWh BESS’ participate in the DS3 program, prices go down and multiple services are provided, it is also profitable to invest in these storages.
Keywords: gas turbines; electricity market; costs; energy market; batteries; fi=Energiatekniikka|en=Energy Technology|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|; Energiatekniikka